Urbanization-induced spatio-temporal variation of water resources utilization in northwestern China: A spatial panel model based approach - Lan Mu (Elsevier, 2021)
Rapid urbanization has become a common occurrence worldwide, and it is important to ensure a sustainable water supply despite the increasing severity of water resource constraints. As an important area along the one belt and one road line, northwest China has experienced increasing water shortages during the rapid urbanization process in recent decades. In the current work, we employed the Spatial Panel Econometric Model to explore the spatial influence of urbanization on water resource utilization and its driving mechanism (e.g., economy, population, trade, capital, investment and industry structure) based on the water ecological footprint perspective during the period from 2005 to 2017. The results indicated that urbanization and the water ecological footprint showed a spatially clustered trend. In addition, the spatial lag regression coefficient of ρ in the spatial Durbin model was significant at the 1% level, showing that the water ecological footprint had an obvious spatial spill-over effect. Urbanization reduced the water ecological footprint in northwest China, and the main driving factors were the economic scale effect, population scale effect and investment pull effect. However, human capital exhibited a significantly positive relationship with the water ecological footprint, which was contrary to our theoretical hypothesis. In the classification of the water ecological footprint, urbanization reduced the agricultural water ecological footprint both temporally and spatially, while the other classifications all increased. The results are beneficial for informing policies towards sustainable water resource utilization under the framework of integrated development in the process of rapid urbanization in northwest China.